Skin innervation: important roles during normal and pathological cutaneous repair - Laverdet, Betty; Danigo, Aurore; Girard, Dorothée; Magy, Laurent; Demiot, Claire; Desmoulière, Alexis (Histology and histopathology, 2015)
The skin is a highly sensitive organ. It is densely innervated with different types of sensory nerve endings, which discriminate between pain, temperature and touch. Autonomic nerve fibres which completely derive from sympathetic (cholinergic) neurons are also present. During all the phases of skin wound healing (inflammatory, proliferative and remodelling phases), neuromediators are involved. Several clinical observations indicate that damage to the peripheral nervous system influences wound healing, resulting in chronic wounds within the affected area. Patients with cutaneous sensory defects due to lepromatous leprosy, spinal cord injury and diabetic neuropathy develop ulcers that fail to heal. In addition, numerous experimental observations suggest that neurogenic stimuli profoundly affect wound repair after injury and that delayed wound healing is observed in animal models after surgical resection of cutaneous nerves. All these observations clearly suggest that innervation and neuromediators play a major role in wound healing. Interactions between neuromediators and different skin cells are certainly crucial in the healing process and ultimately the restoration of pain, temperature, and touch perceptions is a major challenge to solve in order to improve patients' quality of life.